Effects of passaging and different glucose concentrations on growth of the planktonic cell and biofilm formation ability among Candida glabrata strains - Nurhairulamri Kosnan.
The opportunistic fungal pathogen Candida glabrata which is present in the human body as microflora has a remarkable ability to adapt to unfavourable environments through different mechanisms, including microevolution. Multiplying C. glabrata for experimental purposes involving many passage numbers may exhibit this adaptation that leads to new phenotypic characteristics. Unrevealed effects of passaging on C glabrata has not been extensively studied. Glucose is the main fuel source for C. glabrata in their physiological fitness and pathogenicity. Glucose consumption ability in varying concentration affected by physiological changes after some adaptation may influence their growth rate along with the ability to form biofilrn formation. Microevolution demonstrated by C. glabrata indeed exhibits genetic modification which becomes phenotypically evident for their changes. This study aims to demonstrate the impact of passaging and glucose concentration on the growth and biofilm formation ability of Candida glabrata. It is hypothesised that the growth rate and ability to form bio-film of C. glabrata are influenced by glucose concentration and passage numbers. C. glabrata strains from blood and vaginal isolates were cultured in defined glucose concentration (0.01%, 0.1% and 2%) and underwent passaging until thirty times. Each glucose concentration from each isolates strains was performed in triplicate for every assays. Passage numbers (0, 10, 20 and 30) were assessed with several assays to determine the physiological changes occurred. The growth rate of C. glabrata which correlates to the amount of glucose was determined by employing growth profiling assay. To determine whether C. glabrata has the ability of fine-turning its life style in bio-film formation activity, XTT {2,3-Bis(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide) reduction assay was used to analyse its metabolic activity. Statistical analysis were performed using two-way ANOVA and unpaired t-test with p-value less than (p<0.05) considered as a significant effect. The growth rate and biofilm formation activity of the strains correlated positively to the amount of glucose even after undergoing through several number of passages. In addition, variability in growth pattern indicated the impact of passaging that might cause the physiological adaptation of the species. Conversely, increase in passage numbers was found to significantly reduce its ability to form bio-film as it might have lost important physiological characteristics in their genome or inactivation of individual-related genes. These observations demonstrated the impact of passaging and glucose on C. glabrata that contribute to microevolution and physiological changes which differentiate the laboratory reference strains from clinical isolates. Thus, the interpretation of any study result must not only consider the experimental conditions but the background of the strains used and should underline the selective disadvantages of conventional laboratory growth conditions for C. glabrata strain. Keywords: Candida glabrata, microevolution, adaptation, passaging, glucose, growth, bio-film formation, physiological characteristic, conventional laboratory growth condition